A review relations of optical tomography and optical coherance tomography - Rahman N.A.A.; Hong L.E.; Rahim R.H.A.; Yunus M.A.M.; Wahab N.A.; Ahmad N.; Wahab A.R.; Jumaah M.F.; Hong L.E.; Loon G.C.; San C.K.; Juliza Jamaludin (Penerbit UTM Press, 2024)
Indexed by WOS/Scopus